Labour, Liberalism, and the Democratic Party: A Vexed Alliance - Lichtenstein, Nelson (Relations industrielles / Industrial Relations, 2011)
The American trade union movement constitutes a social democratic bloc within U.S. politics. Often successful in expanding the welfare state, American unions have almost always failed to win legislation advancing their institutional strength and political legitimacy. This has been particularly true during the prosperous postwar era (1947-1979) when a depoliticalized form of collective bargaining stood at the centre of the U.S. system of industrial accommodation and conflict. But today that system is ineffectual, forcing the trade unions to return to a system of state-centred, corporatist bargaining reminiscent of that which sustained the unions during the era of the late New Deal and World War II. But this 21~ century system is a weak and tenuous version of corporatism, largely and dangerously confined to local government and those industries dependent on the state for revenue and regulation.
Keywords: Alliances; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Collective bargaining; Labor Unions; Liberalism; Political parties; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z